2014
DOI: 10.5897/jmpr2013.5207
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antimicrobial activity of the stem-bark of Gardenia aqualla Stapf Hutch (Rubeacea)

Abstract: Gardenia aqualla Stapf & Hutch (Rubeacea) is a plant belonging to the family Rubeacea. Preliminary phytochemistry carried out on the methanolic (ME) extract of the stem bark revealed the presence of steroid, carbohydrates, anthraquinones, saponins, triterpenes, tannins, cardiac glycoside and flavonoid while the petroleum ether (PE) extract of the stem bark revealed the presence of steroid, triterpenes and flavonoids. The PE extract and the ME were evaluated for antimicrobial screening using agar diffusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The antibacterial activity of extracts was evaluated using disc diffusion method (EUCAST, 2012). MIC and MBC of leaf extracts were determined by agar dilution method as described in EUCAST (2000) and Njinga et al (2014), respectively. The bacterial suspension adjusted to 1.5 x 10 8 CFU/mL was inoculated to the Petri dishes containing YPSA growth medium using cotton swab.…”
Section: Antibacterial Activity Of Leaf Extractsmentioning
confidence: 99%
“…The antibacterial activity of extracts was evaluated using disc diffusion method (EUCAST, 2012). MIC and MBC of leaf extracts were determined by agar dilution method as described in EUCAST (2000) and Njinga et al (2014), respectively. The bacterial suspension adjusted to 1.5 x 10 8 CFU/mL was inoculated to the Petri dishes containing YPSA growth medium using cotton swab.…”
Section: Antibacterial Activity Of Leaf Extractsmentioning
confidence: 99%
“…Minimum bactericidal concentration (MBC) of leaf extracts was determined as described in Njinga et al (2014). Serial test concentrations of each species extract were prepared.…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%
“…Studies have shown that the phytochemistry of the methanolic extract of stem bark of G. aqualla revealed the presence of steroid, carbohydrate, anthraquinones, saponins, triterpenes, tannins, cardiac glycoside and flavonoids. The antimicrobial activity of this plant indicates that the plant can be used as traditional medicine [12][13][14]. Hence, the leaves, roots, fruits and stem bark is used to treat leprosy, oral infection, ear infection and bowel disorder respectively in Northern Nigeria [15].…”
Section: Introductionmentioning
confidence: 99%